“I can barely manage myself, how could I possibly care for someone else?”: Women´s with physical disabilities expectations in relation to the ideal of Motherhood (Palimpsesto, 2025)
Feminist perspectives have highlighted the inadequacy of equating womanhood with reproductive function and motherhood as an inevitable destiny. However, this equivalence does not hold for disabled women: in contrast to the socially constructed ideal of motherhood, their capacity to reproduce and/or care for others is often questioned.Based on in-depth interviews with cisgender, heterosexual, physically disabled women living in the Metropolitan Area of Buenos Aires, this article explores their expectations regarding motherhood. These women describe motherhood as a goal that is difficult to achieve or even to envision, due to their impairments, various fears, lack of economic security, and emotional dimensions, such as perceived risk and selfishness, which shape and regulate their expectations.
Keywords: Motherhood; Disability; Affects; Gender; Embodiment